A meta-analysis of nutrient intake, feed efficiency and performance in cattle grazing on tropical grasslands. (20th January 2015) - Boval, M.; Edouard, N.; Sauvant, D.
Abstract : It is essential to quantify the potential of tropical grasslands to allow significant feed efficiency for grazing livestock in controlled conditions such as at pasture. We conducted a quantitative analysis of published studies reporting the experimental results of average daily gains (ADG) and diet characteristics obtained specifically under grazing conditions (17 publications and 41 experiments), which have been less studied compared with controlled conditions in stalls. The database was analyzed to determine the average and range of values obtained for ADG (g/kg BW), dry matter digestibility, intake (DMI) and digestible DMI (DDMI, g/kg BW) and feed conversion efficiencies (FCE), as well as to predict the response of these parameters to the main strategies investigated in the literature – that is, mainly the stocking rate (SR) and the concentrate intake (CI). The ADG reached 1.2 kg BW per day and was directly linked to DDMI (ADG=−1.63+0.42 DDMI −0.0084 DDMI 2, n =90, r.m.s.e=0.584, R 2 =0.93). The DDMI, which was representative of the nutrient input, was driven mainly by DMI rather than dry matter digestibility, whereas these two parameters did not correlate ( r =0.068, P =0.56). The average global FCE (0.11 g ADG/g DDMI) showed a greater association with the metabolic FCE (0.17 g ADG/g DMI) than the digestive FCE (0.62). The CI (g DM/kg BW) increased ADG (ADG=2376+CI 56.1, n =16, r.m.s.e.=441, R 2 =0.95). The SR expressed as kg BW/ha decreased the individual ADG by 1.19 g/kg BW per additional ton of BW/ha, whereas the global ADG calculated per ha increased by 0.57 per additional ton BW/ha. When the SR was expressed as kg BW/ton DM and per ha rather than as kg BW/ha, the impact on the individual ADG decreased by 0.18 or 0.86 g per additional ton BW/ha, depending on the initial BW of the cattle. These results provide a better view of the potential performance and feeding of cattle in tropical grasslands. The results provide an improved quantification of the relationships between diet and performance, as well as the overall quantitative impact of SR and supplementation.